UNDERSTANDING ENGLISH LANGUAGE TEACHING IN EFL CONTEXT from idea to practicality. - Kamal-ud-din. ([S.l.] : ROUTLEDGE, 2023)
This volume is comprehensively designed to help prospective English Language Teaching (EFT) teachers specializing in Englishas a foreignlanguage (EFL) mainly in South Asian countries. It analyses the application of ELT theories, concepts, and methods to sharpen their understanding of the various techniques used for teaching English effectively in the EFL context. The book discusses the basic concepts of language aimed to develop a sense of the language phenomenon as a unique human attribute. It covers the theories of language from various disciplines such as biology, sociology, psychology, and linguistics. The book explains the underlying structures or components that shape the edifice of languages such as phonology, morphology, syntax, grammar, phonetics, semantics, and pragmatics. While taking the reader through language learning theories with a focus on English as the second language, it discusses the different teaching methods that can be adopted by teachers in classroom settings. The book will be of interest to teachers, students and researchers of education, teacher education, and ELT. It will also be useful for educators, English language teachers, language learners, professionals working in the field of education and language, and those who aspire to teach and learn English in foreign context.
Keywords: English language -- Study and teaching -- Foreign speakers; EDUCATION / General; FOREIGN LANGUAGE STUDY / General; FOREIGN LANGUAGE STUDY / English as a Second Language